EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA KALINAUN KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - KAWOWODE, OLIVIA; TAMPI, GUSTAAF BUDI; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: The realization of village funds is a follow-up to the government's program of building Indonesiafrom the periphery by strengthening the regions and villages within the framework of the Unitary State of theRepublic of Indonesia aimed at improving the welfare and equity of development through improving publicservices, promoting the economy, overcoming the inter-village development gap and strengthening thecommunity as subject of development. The purpose of this study is to determine the extent of effectiveness ofvillage fund management in Kalinaun Village, East Likupang District, North Minahasa District. This researchis a descriptive research with qualitative approach. Technique of collecting data in this research is usingobservation method that is direct observation to research location and do interview and documentation. Thefocus of research is the achievement of goals, integration and adaptation. Based on the results of the research,the effectiveness of the management of village funds in Kalinaun Village, East Likupang District, NorthMinahasa Regency, can not be said to be effective because the development done by the government still findssome problems and the development is not done evenly, making social jealousy among the community. TheKalinaun Village Government is also inconsistent with what it deliberates so that people are reluctant to worktogether.Keywords: Effectiveness of Village Fund Management.